Recent progress in nanomaterial-based electrochemical biosensors for pathogenic bacteria - Pourakbari, Ramin; Shadjou, Nasrin; Yousefi, Hadi; Isildak, Ibrahim; Yousefi, Mehdi; Rashidi, Mohammad-Reza; Khalilzadeh, Balal (SPRINGER WIEN, 2019)
This review (with 118 refs.) discusses the progress made in electroanalytical methods based on the use of organic and inorganic nanomaterials for the determination of bacteria, specifically of E. coli, Salmonella, Staphylococcus, Mycobacterium, Listeria and Klebsiella species. We also discuss advantages and limitations of electrochemical methods. Strategies based on the use of aptamers, DNA and antibodies are covered. Following an introduction into electrochemical biosensing, a first large section covers methods for pathogen detection using metal nanoparticles, with subsections on silver nanoparticles, gold nanoparticles, magnetic nanoparticles and carbon-based nanomaterials. A second large section covers methods based on the use of organic nanocomposites, graphene and its derivatives. Other nanoparticles are treated in a final section. Several tables are presented that give an overview on the wealth of methods and materials. A concluding section summarizes the current status, addresses challenges, and gives an outlook on potential future trends.
Keywords: Bioassay; Metal nanoparticles; Carbon allotropes; Graphene; Carbon nanotubes; Nanocomposite; Biotechnology; Polymeric nanoparticles; SURFACE-PLASMON RESONANCE; ESCHERICHIA-COLI O157H7; GLASSY-CARBON ELECTRODE; COATED MAGNETIC BEADS; LABEL-FREE DETECTION; SILVER NANOPARTICLES; GOLD NANOPARTICLES; DNA BIOSENSOR; SENSITIVE DETECTION; MYCOBACTERIUM-TUBERCULOSIS; Chemistry